Two Classes of Integrals Involving Extended Wright Type Generalized Hypergeometric Function - Ghaffar, A.; Saif, A.; Iqbal, M.; Rizwan, M. (Communications in Mathematics and Applications, 2019)
In this article, our main purpose is to investigate generalized integral formulas containing the extended Wright type generalized hypergeometric function. Moreover, certain special cases of the main results given here have also been pointed out for the Wright type hypergeometric function.